[Finished exterior of Kennedy Library] - P. K. Phillips::::::photographer::: (1978)
Construction of Kennedy Library, later into the process. The finished exterior and main entrance are pictured, fenced in and surrounded by construction materials. A person walks on the sidewalk opposite of the building.